2000
DOI: 10.1590/s0100-879x2000000400004
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intercellular communication by differential regulation and heteromeric mixing of co-expressed connexins

Abstract: Intercellular communication may be regulated by the differential expression of subunit gap junction proteins (connexins) which form channels with differing gating and permeability properties. Endothelial cells express three different connexins (connexin37, connexin40, and connexin43) in vivo. To study the differential regulation of expression and synthesis of connexin37 and connexin43, we used cultured bovine aortic endothelial cells which contain these two connexins in vitro. RNA blots demonstrated discordant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 14 publications
2
17
0
2
Order By: Relevance
“…In addition, hemichannels can be composed of one (homomeric channels) or a mixture (heteromeric channels) of connexin proteins. Homomeric channels formed by different connexin isoforms typically differ in unitary conductance, permeability, and regulation and, as expected, the mixture of connexins in a heteromeric channel results in unique communication properties (28,84,131,141), which provide an additional mechanism for fine regulation of gap junction-mediated signaling processes (12,129,204).…”
supporting
confidence: 57%
“…In addition, hemichannels can be composed of one (homomeric channels) or a mixture (heteromeric channels) of connexin proteins. Homomeric channels formed by different connexin isoforms typically differ in unitary conductance, permeability, and regulation and, as expected, the mixture of connexins in a heteromeric channel results in unique communication properties (28,84,131,141), which provide an additional mechanism for fine regulation of gap junction-mediated signaling processes (12,129,204).…”
supporting
confidence: 57%
“…Connexin channels are homo-or hetero-oligomers of isoforms of connexin protein (23)(24)(25)(26)(27). Connexin channels have two functional and structural forms.…”
mentioning
confidence: 99%
“…Thus, although these proteins may have some overlap in function, they work in concert (Simon & Goodenough, 1998;Figueroa et al, 2004Figueroa et al, , 2006Haefliger et al, 2006) and, consequently, it has been observed that many times the function of one connexin cannot be replaced by other connexin isoform (White, 2003;Haefliger et al, 2006;Zheng-Fischhofer et al, 2006;Wolfle et al, 2007). In addition, hemichannels can be composed by one or a mixture of connexin proteins, which provides an additional mechanism for fine regulation of gap junction-mediated signaling processes (White & Bruzzone, 1996;He et al, 1999;Beyer et al, 2000;Cottrell et al, 2002;Moreno, 2004).…”
Section: Gap Junction Communication In the Vascular Functionmentioning
confidence: 99%